2015
DOI: 10.3389/fmicb.2015.00860
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of aerobic cultivable cellulolytic bacteria from different regions of the gastrointestinal tract of giant land snail Achatina fulica

Abstract: The enzymatic hydrolysis of cellulose by cellulases is one of the major limiting steps in the conversion of lignocellulosic biomass to yield bioethanol. To overcome this hindrance, significant efforts are underway to identify novel cellulases. The snail Achatina fulica is a gastropod with high cellulolytic activity, mainly due to the abundance of glycoside hydrolases produced by both the animal and its resident microbiota. In this study, we partially assessed the cellulolytic aerobic bacterial diversity inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Several researchers reported Stenotrophomona sp. as cellulolytic (Huang et al, 2012; Talia et al, 2012; Pinheiro et al, 2015). In addition, members of Micrococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers reported Stenotrophomona sp. as cellulolytic (Huang et al, 2012; Talia et al, 2012; Pinheiro et al, 2015). In addition, members of Micrococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…I1.2 Cultivation for Enzyme Production Streptomyces sp. strain I1.2 was isolated from the intestinal lumen of the land snail A. fulica in a screening for cultivable cellulolytic aerobic bacteria [17]. Firstly, Streptomyces sp.…”
Section: Methodsmentioning
confidence: 99%
“…These include endo-glucanases from Helix pomatia [49], from Dolabella auricularia [50], and more recently, from Ampullaria crossean [51] and Pomacea canaliculata [52]. In addition to their endo-genous enzymatic repertoire, recent studies revealed that land snails contain a complex and adaptable microbiota that potentially accounts for their great digestive efficiency [17,53,54]. In addition, a metagenomic analysis of A. fulica crop-resident microbiota identified a great number of sequences coding for biomass-degrading enzymes (36 %), including cellulases and hemicellulases [45].…”
Section: In Complexes C-[i] C-[ii] and C-[iii]mentioning
confidence: 99%
See 1 more Smart Citation
“…The colony formed on the solid medium of C4 strain is white and its diameter was about 1 mm. The edge of colony was zigzag, and there was a large degrading circle around it showing good degradability of cellulose [26] . As shown in Fig.…”
Section: Isolation and Identification Of Strainsmentioning
confidence: 99%